Key concepts of medical physiology - Chatterjee, Amar; Chatterjee, Rita; Mohd Hamim Rajikin (UiTM Press, 2013)
This book contains 56 chapters with glossaries and each chapter is written with utmost care to provide updated information in the respective topic in human medical physiology